Micromechanics of Fracture Propagation and Seismic Source Parameters in Ceramics Made of Gold Mine Tailings - Farid Shabani; Awais Butt; Ahmadreza Hedayat; Juan Antonio Vega Gonzalez; Jorge Wilfredo Vera Alvarado; Martin Taboada Neira (Rock Mechanics and Rock Engineering, 2026)

Evaluation of Fracture Properties in Ceramics Made of Sulfidic Mine Tailings - Farid Shabani; Mostafa Asadizadeh; Ahmadreza Hedayat; Lori Tunstall; Brian P. Gorman; Juan Antonio Vega Gonzalez; Jorge Wilfredo Vera Alvarado; Martin Taboada Neira (Rock Mechanics and Rock Engineering, 2026)

Composition, Diversity, and Biomass of Scarabaeoidea in Tropical Dry Forests of the Colombian Caribbean Region - Carlos Taboada-Verona; Rafael Narváez; Jorge Ari Noriega (Neotropical Entomology, 2026)
Knowing the spatial variability of a region helps us develop specific conservation strategies to mitigate human-induced disturbances. In this context, beetles are excellent bioindicators of spatial changes resulting from human disturbance. This work aims to determine the spatial heterogeneity of the diversity of the superfamily Scarabaeoidea in dry forests of the Colombian Caribbean region. Individuals were captured using baited flight interception traps, pitfall traps, fruit-baited traps, manual collection, and light traps. Forty-seven species, 23 genera, and four families were recorded; the dominant species were Sylvicanthon aequinoctialis (Harold, 1868), Eurysternus caribaeus (Herbst, 1789), and Ateuchus sp. 1. Sampling completeness was above 99%. The range-abundance curves show that the structure is similar between the three sampling sites, presenting very steep slopes, indicating low equity. The dominant trophic guilds were coprophages, constituting 53% of all species, followed by necrophages and sapro-xylophages, with 17% and 15%, respectively. Regarding alpha diversity, the sites showed a pattern of high richness, while beta diversity showed a dissimilarity of 38%. For biomass, no significant differences were detected. The variation in diversity in the study sites may be related to low spatial heterogeneity. Some families are subject to spatio-temporal variability, reproduction cycles, and trap effectiveness. Although this region is under different anthropogenic pressures, such as deforestation, livestock, tourism, and monocultures, the beta diversity of the superfamily Scarabaeoidea was homogeneous in terms of the pattern in the sites studied here. Finally, the composition, diversity, and biomass of the subfamily Scarabaeoidea are potential indicators of spatial heterogeneity in disturbed landscapes.

Indirect monitoring of heterogeneous tropical agroforestry systems using active and passive remote sensing - Teiser Sánchez-Fuentes; Darwin Gómez-Fernández; Jorge A. Fernandez-Jibaja; Jhon F. Oblitas-Troyes; Beimer Chuquibala-Checan; Josué Tafur-Culqui; Rosalia Quichua-Baldeon; Victor H. Taboada-Mitma; Daniel Tineo; Malluri Goñas; Nilton Atalaya-Marin (Remote Sensing Applications: Society and Environment, 2026)

Estimation of aboveground biomass and carbon sequestration in a cocoa agroforestry system using UAV-LiDAR in northwestern Peru - Nilton Atalaya-Marin; Teiser Sanchez-Fuentes; Malluri Goñas; Daniel Tineo; Victor H. Taboada-Mitma; Héctor Cabrera-Hoyos; JuanCarlos Cruz-Luis; Jorge J. Ganoza-Roncal; Darwin Gómez-Fernández (Remote Sensing Applications: Society and Environment, 2025)

H2O2-generating polyamine oxidases (PAOs) are modulated during sweet pepper ripening: Spermine oxidase (SpmOX) as a case study of post-translational modification regulation - María A. Muñoz-Vargas; Jorge Taboada; José M. Palma; Francisco J. Corpas (Plant Science, 2025)

Activity and gene expression analysis of the NADP-dependent isocitrate dehydrogenase (NADP-ICDH) through pepper fruit ripening and its modulation by nitric oxide (NO). Molecular characterization of the peroxisomal isozyme - María A. Muñoz-Vargas; Salvador González-Gordo; Jorge Taboada; José M. Palma; Francisco J. Corpas (Plant Science, 2024)

Characterization of leucine aminopeptidase (LAP) activity in sweet pepper fruits during ripening and its inhibition by nitration and reducing events - María A. Muñoz-Vargas; Jorge Taboada; Salvador González-Gordo; José M. Palma; Francisco J. Corpas (Plant Cell Reports, 2024)
Key message Pepper fruits contain two leucine aminopeptidase ( LAP ) genes which are differentially modulated during ripening and by nitric oxide. The LAP activity increases during ripening but is negatively modulated by nitration . Abstract Leucine aminopeptidase (LAP) is an essential metalloenzyme that cleaves N-terminal leucine residues from proteins but also metabolizes dipeptides and tripeptides. LAPs play a fundamental role in cell protein turnover and participate in physiological processes such as defense mechanisms against biotic and abiotic stresses, but little is known about their involvement in fruit physiology. This study aims to identify and characterize genes encoding LAP and evaluate their role during the ripening of pepper ( Capsicum annuum L.) fruits and under a nitric oxide (NO)-enriched environment. Using a data-mining approach of the pepper plant genome and fruit transcriptome (RNA-seq), two LAP genes, designated CaLAP1 and CaLAP2 , were identified. The time course expression analysis of these genes during different fruit ripening stages showed that whereas CaLAP1 decreased, CaLAP2 was upregulated. However, under an exogenous NO treatment of fruits, both genes were downregulated. On the contrary, it was shown that during fruit ripening LAP activity increased by 81%. An in vitro assay of the LAP activity in the presence of different modulating compounds including peroxynitrite (ONOO − ), NO donors ( S -nitrosoglutathione and nitrosocyteine), reducing agents such as reduced glutathione (GSH), l -cysteine ( l -Cys), and cyanide triggered a differential response. Thus, peroxynitrite and reducing compounds provoked around 50% inhibition of the LAP activity in green immature fruits, whereas cyanide upregulated it 1.5 folds. To our knowledge, this is the first characterization of LAP in pepper fruits as well as of its regulation by diverse modulating compounds. Based on the capacity of LAP to metabolize dipeptides and tripeptides, it could be hypothesized that the LAP might be involved in the GSH recycling during the ripening process.

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

An updated life‐history scheme for marine fishes predicts recruitment variability and sensitivity to exploitation - Colleen M. Petrik; Fernando González Taboada; Charles A. Stock; Jorge L. Sarmiento (Global Ecology and Biogeography, 2021)
Aim Patterns of population renewal in marine fishes are often irregular and lead to volatile fluctuations in abundance that challenge management and conservation efforts. Here, we examine the relationship between life‐history strategies and recruitment variability in exploited marine fish species using a macroecological approach. Location Global ocean. Time period 1950–2018. Major taxa studied Bony and cartilaginous fish. Methods Based on trait data for 244 marine fish species, we extend the established equilibrium–periodic–opportunistic ( E‐P‐O ) life‐history classification scheme objectively to include two additional emergent life‐history strategies: “bet‐hedgers” ( B ) and salmonic ( S ) strategists. The B strategists include rockfishes and other species inhabiting patchy benthic habitats with life histories that blend characteristics of E and P species; they combine very long life spans with elevated investments in both parental care and fecundity. The S strategists mainly comprise salmonids that share life‐history characteristics with E and O species: elevated investments in parental care reminiscent of E strategists, but with reduced fecundity and short life spans characteristic of O species. We analysed how the E‐B‐P‐O‐S life‐history classification mapped onto patterns of recruitment variability observed in population time series data ( n = 156 species). Results Generalized linear models suggested that life‐history strategy explained a modest, yet significant amount of recruitment variability across species. Greater predictive power arose after controlling for increased recruitment variance associated with variable fishing pressure, with O strategists showing the strongest sensitivity. The B strategists were susceptible to exploitation in a similar manner to P stocks, but their longer times to maturity made them particularly vulnerable to overfishing. Main conclusions A broader recognition of the distinct ecology of salmonic and bet‐hedger groups is important when studying life‐history strategies in marine fish. More generally, our results stress the importance of considering life‐history strategies for understanding patterns of recruitment variability across fish stocks.